(untitled) (Journal of Economic Research & Business Administration, 2015)
Бұл мақалада ұйымның шоғырландырылған қаржылық есептілігінің экспресс талдауы қарастырылған. *** Express-analysis of the consolidated financial statements of the organization is considered in this article.